Study on the performance of calcined spent waterglass foundry sand in alkali-activated foam concrete. (16th May 2023) - Liu, Chenxu; Wang, Changbai; Xiao, Wei; Wu, Jianyang; Gao, Mengcheng
Highlights: SwFS calcined at 900 °C was used as AAFC aggregate. Characterisation of AAFC using thermal conductivity, MIP, and SEM. SwFS 9 replaces quartz sand can lower the fluidity of AAFC. Mechanical properties of AAFC with SwFS 9 are higher than those without SwFS 9 . Incorporating SwFS 9 can reduce the AAFC thermal conductivity. Abstract: The resource utilization of spent foundry sand (SFS) helps solve environmental problems and reduce construction costs. Using SFS as fine aggregate incorporated into concrete for practical application has recently become a research hotspot. However, researchers are rarely concerned about the application of SFS in alkali-activated foamed concrete (AAFC). AAFC is a lightweight concrete material with excellent thermal insulation and fire resistance while reducing CO2 emissions. In this paper, spent foundry waterglass sand (SwFS) calcined at 900 °C replaced fine aggregates (0%, 20%, 40%, 60%, 80%, 100%) to prepare AAFC. This paper studied the performance of calcined SwFS in alkali-activated foam concrete. The experimental results show that the SwFS suffered calcined at 900 °C release SiO3 2− at slow speeds in AAFC and can be an auxiliary activator for AAFC. In addition, the compressive strength of AAFC with SwFS added to 900 °C increased by 15% ∼ 29% and 15% ∼ 25% at 3 d and 7 d, respectively, and decreased slightly at 28 d.